2016
DOI: 10.1364/oe.24.012281
|View full text |Cite
|
Sign up to set email alerts
|

Excitation mechanism of A_1g mode and origin of nonlinear temperature dependence of Raman shift of CVD-grown mono- and few-layer MoS_2 films

Abstract: MoS2 films are grown on SiO2/Si substrates by chemical vapor deposition. The vibrational properties of optical phonons of mono-, bi- and multilayer MoS2 are studied by Raman scattering spectroscopy over temperature range from 90 to 540 K with 514.5 nm and 785 nm lasers. The Raman peaks of E2g1 and A1g modes are observed simultaneously for mono-, bi- and multilayer MoS2 with 514.5 nm laser, but only the Raman peak of E2g1 mode is seen for monolayer MoS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“… where, ω 0 and ω are the initial and shifted wave number respectively. We have taken γ = 0.21 and γ (A 1g ) = 0.42 27 , 28 . As previously discussed, both and A 1g modes in MoS 2 are very sensitive to fluence of ion beam irradiation.…”
Section: Resultsmentioning
confidence: 99%
“… where, ω 0 and ω are the initial and shifted wave number respectively. We have taken γ = 0.21 and γ (A 1g ) = 0.42 27 , 28 . As previously discussed, both and A 1g modes in MoS 2 are very sensitive to fluence of ion beam irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature dependent phonon frequency is phenomenologically described as ∆ω = χ∆T where ∆ω is the frequency shift and χ is a phonon shift per Kelvin. For MoS 2 there is a consensus in the literature that χ ∼ −0.01 cm −1 /K [42,53,54] (see Table 1). Interestingly, this number is largely independent of the substrate and holds also for freestanding layers [44].…”
Section: Vibrational Properties and Strainmentioning
confidence: 99%
“…concluded that the threephonon process are irrelevant in explaining the observed phonon-frequency shifts of Raman active modes, whereas Yang et-al. found the three-phonon processes to be more dominant [32,33]. Lanzillo et-al.…”
Section: Introductionmentioning
confidence: 96%
“…Even after intense research for more than a decade, an arXiv:2009.04206v1 [cond-mat.mes-hall] 9 Sep 2020 in-depth, combined experimental and theoretical study of the temperature evolution of the phonon-modes; in single-and few-layer MoS 2 is missing. Previous studies employed semi-quantitative models for the calculation of the temperature dependent Raman shift [32,33]. Two contradictory conclusions have been reported by fitting the experimental data to such models for 300 K< T <500 K. Najmei et-al.…”
Section: Introductionmentioning
confidence: 99%